Postnatal Light Effects on Pup Stress Axis Development Are Independent of Maternal Behavior - Coleman, Georgia; Canal, Maria M. (Frontiers in Neuroscience, 2017)
Postnatal environment shapes brain development during key critical periods. We have recently found that postnatal light environment has long-term effects on the stress and circadian systems, which can lead to altered stress responses, circadian behavior and a depressive phenotype in adulthood. However, it is still unclear how light experience affects the postnatal development of specific stress markers in the pup brain and the role played by maternal behavior and stress. To test this, we raised mice under either light-dark cycles (LD), constant light (LL) or constant darkness (DD) during the suckling stage. After weaning, all mice were exposed to LD until adulthood. Results show that postnatal light environment does not have any significant effects on dam stress levels (plasma corticosterone concentration, Arginine-vasopressin and Glucocorticoid receptor (GR) protein expression in the brain) or maternal behavior, including licking and grooming. Light environment does not have a major effect on litter characteristics or pup growth either. Interestingly, light environment during the suckling stage significantly impacted Corticotrophin-releasing hormone (CRH) and Gr mRNA expression in pup brain during development. Furthermore, a difference in Crh mRNA expression between LL- and DD-raised mice was still observed in adulthood, long after the exposure to abnormal light environments had stopped. Taken together, these data suggest that the long-term effects of postnatal light environment on the pups’ stress system cannot be attributed to alterations in either maternal behavior and/or stress axis function. Instead, postnatal light experience may act directly on the pup stress axis and/or indirectly via circadian system alterations.